THE IMPLEMENTATION OF A CANVA-BASED E-PORTFOLIO: ITS IMPACT ON ACHIEVEMENT, SELF-EFFICACY, AND ANXIETY IN ESP-WRITING INSTRUCTION - Budi, Beni Setya; Anwar, Khoirul (University of Kuningan, 2024)
English for Specific Purposes (ESP) learners derive significant advantages from a writing method that focuses on the process rather than just the end result. This need is emphasized by the fact that teachers often do not prioritize the optimization of this technique while teaching ESP writing workshops. This approach focuses on the different stages of text creation and is used in educational settings to give students clear guidance. It helps them go through a genuine writing process, boosts their confidence, reduces anxiety, and includes activities that support writing, such as choosing the right media. This study examines the influence of integrating Canva and e-portfolio on the writing proficiency of Agriculture students in an English for Specific Purposes (ESP) setting. The study also investigates the impact of this integration on students' self-efficacy and anxiety levels during the learning process. This is done through a mixed-method approach that incorporates before and post-tests, writing assignments, and post-treatment questionnaires. The implementation of Canva-based E-portfolios in teaching English for Specific Purposes (ESP) has yielded encouraging outcomes, as seen by improved posttest scores in both the control and experimental groups. Notably, the experimental group demonstrated a significant enhancement, indicating the potential advantages of broader utilization. The intervention demonstrates a positive impact on students' self-efficacy and reduces their anxiety levels, suggesting its effectiveness in ESP classrooms. However, additional research is needed to validate these findings and investigate the specific factors that contribute to this improvement